Proceedings of the 2017 Conference on Conference Human Information Interaction and Retrieval 2017
DOI: 10.1145/3020165.3022162
|View full text |Cite
|
Sign up to set email alerts
|

Building Cost-Benefit Models of Information Interactions

Abstract: Modeling how people interact with search interfaces has been of particular interest and importance to the field of Interactive Information Retrieval. Recently, there has been a move to developing formal models of the interaction between the user and the system, whether it be to: (i) run a simulation, (ii) conduct an economic analysis, (iii) measure system performance, or (iv) simply to better understand the interactions and hypothesise about user behaviours. In such models, they consider the costs and the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We report the classification result in Table 1. We found that the F1-score of the "uninterested" collection of images is significantly higher than the "interested" list of items which is due to the diminishing return of information scent score (in line with [1]). It means that the user selected item in first glance put less effort (selection cost) and those followed several iteration on user preferences to select an image results in weak information scent (and ranked lower in the list of interesting items).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…We report the classification result in Table 1. We found that the F1-score of the "uninterested" collection of images is significantly higher than the "interested" list of items which is due to the diminishing return of information scent score (in line with [1]). It means that the user selected item in first glance put less effort (selection cost) and those followed several iteration on user preferences to select an image results in weak information scent (and ranked lower in the list of interesting items).…”
Section: Resultsmentioning
confidence: 66%
“…In Information Foraging Theory, the flux of information in an information environment perceives user plans for seeking, gathering and consumption based on their utility [16]. The view of animals 1 A board allows people to place all of their visual cues around diverse interests, ideas and plans 2 Foraging phenomena in this work refers to Information Foraging Theory following scents to forage is analogous to users following various kinds of cues, assessing information contents and navigating across information spaces depending on their information scent. Cues cater as proximal cues in order to emit information scent.…”
Section: Implicit Feedback Signals 41 Cues As Artifacts Of Informatimentioning
confidence: 99%
“…To determine whether the boost function achieves this aim we use a cost model inspired by Järvelin (2009) and compare the cost before the introduction of this variable (the intervention) with the cost after the intervention. Azzopardi (2017) and Azzopardi and Zuccon (2016) have used such cost based models to determine the effectiveness of changes to the user interface. This model will be limited to cost without gain, as there are no relevance judgments to base gain on.…”
Section: Discussionmentioning
confidence: 99%
“…Leif and Guido have presented related courses at ACM SIGIR 2015 [5], ACM CIKM 2016, ACM ICTIR 2016 [6] and ACM CHIIR 2017 [4]. They have also recently contributed a chapter on building economic models of interaction to the book "Computational Interaction" published in 2018 [8] which this course draws upon.…”
Section: Instructors Backgroundmentioning
confidence: 99%